2021
DOI: 10.3233/jad-210424
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Training Prevents Memory Deficit Related to Amyloid-β Protein-Induced Neurotoxicity

Abstract: Background: Alzheimer’s disease (AD) is characterized by the accumulation of the amyloid-β peptide in the brain, leading to early oxidative stress and neurotoxicity. It has been suggested that physical exercise could be beneficial in preventing AD, but studies with multicomponent training are scanty. Objective: Verify the effects of multicomponent exercise training to prevent deficits in recognition memory related to Aβ neurotoxicity. Methods: We subjected Wistar rats to multicomponent training (including aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…36 There were some reports that exercise reduces beta-amyloid deposition and prevents amyloid-β-associated neurotoxicity in the brain. [37][38][39] AD participants had low ADL and lack of exercise habits in the present study, and it is suggested that these factors and dementia are related to each other, as in previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…36 There were some reports that exercise reduces beta-amyloid deposition and prevents amyloid-β-associated neurotoxicity in the brain. [37][38][39] AD participants had low ADL and lack of exercise habits in the present study, and it is suggested that these factors and dementia are related to each other, as in previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…Thirdly, clinical and preclinical studies suggest that combining preoperative cognitive training and other interventions likely provides increased benefits for cognitive outcomes. Exercise is one of the most studied interventions and is suggested to improve postoperative cognitive functions when provided alongside cognitive training [86]. Interventions based on the possible pathophysiology of PND, such as the application of anti-inflammatory agents for the prevention of neuroinflammation, will likely be effective when combined with cognitive training [88,89].…”
Section: Discussionmentioning
confidence: 99%
“…Dare et al recently reported that combined physical and cognitive exercise reversed recognition memory deficits for a prolonged period and restored the acetylcholinesterase activity altered by amyloid-β neurotoxicity in the hippocampus in rats [85]. Similarly, multicomponent training, including aerobic and anaerobic physical exercise and cognitive exercise, was shown to prevent memory deficits related to amyloid-β neurotoxicity in the hippocampus in rats by Soares et al [86]. The independent effect of cognitive training is reported to improve performance in memory tasks in ischemia-received rats [87].…”
Section: Preclinical Studiesmentioning
confidence: 94%
“…Some non-pharmacological interventions have been investigated and show promissory effects. Between them, we highlighted the different types of physical exercise, which act by multiple neuroprotective mechanisms (Daré et al, 2020;Soares et al, 2021). However, until now, there is no curative treatment for AD, and researchers are still struggling to find therapeutic targets that promote significant improvements in the clinical conditions of Alzheimer's patients (Knopman et al, 2021).…”
mentioning
confidence: 99%